DETERMINING THE ROLE OF ANGIOGENIC FACTORS IN THE PREDICTION OF PREECLAMPSIA - Navruzova, R.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Preeclampsia is a major cause of maternal and perinatal morbidity and mortality worldwide. Its pathogenesis is complex and multifactorial, involving abnormal placentation, immune dysfunction, and endothelial injury. Recent advances have emphasized the critical role of angiogenic imbalance in the development and progression of preeclampsia. This review evaluates the predictive value of angiogenic biomarkers—including placental growth factor (PlGF), soluble fms-like tyrosine kinase-1 (sFlt-1), and soluble endoglin (sEng)—in identifying women at risk for preeclampsia. It summarizes current evidence on the pathophysiological significance of these factors, their temporal expression patterns in pregnancy, and their integration into clinical risk models. The potential utility of angiogenic biomarkers in early screening, diagnosis, and therapeutic stratification is critically discussed. Incorporating angiogenic profiling into prenatal care could significantly improve the early prediction and management of preeclampsia.